One Family with Cholestasis: The Twisted Road to the Diagnosis of Pfic 3—Three Case Reports - Raluca Maria Vlad; Irina Dijmărescu; Ruxandra Dobritoiu; Andreea Moga; Laura Balanescu; Oana Neagu; Daniela Pacurar (Reports)
Background and Clinical Significance: Progressive familial intrahepatic cholestasis (PFIC) refers to a heterogeneous group of autosomal recessive disorders consisting of mutations of hepatocyte transporting-system genes involved in bile formation. The exact prevalence remains unknown but is estimated at 1 in 500.000 for PFIC 3, caused by mutations in the ABCB4 gene. We report three cases of PFIC 3 from the patient’s sister, brother, and cousin, diagnosed in our Pediatric Department in 2022–2023. Case Presentation: Case 1: A 10-year-old girl was admitted for jaundice and abdominal pain. She was diagnosed with severely advanced hepatic cirrhosis and massive cholestasis. Genetic testing showed ABCB4 homozygous mutation. She rapidly developed fulminant liver failure, and a living donor liver transplant was performed. Case 2: A 6-year-old brother was previously diagnosed with cholestatic hepatitis of unknown cause back in 2018 and presented with similar features (generalized jaundice, severe pruritus with generalized scratching lesions); symptoms had progressively developed from the first year of life. He also exhibited particular facial features (big forehead, twisted ear lobe, straight nose). He received cadaveric liver transplantation. Case 3: Nephew of first two children, a 3-year-5-month-old boy, was admitted for failure to thrive and a one-year history of jaundice, pruritus, and splenomegaly. He was tested positive for homozygous ABCB4 mutation. He is currently under medical treatment with stable liver function. Conclusions: The clinical significance of this particular homozygous variant identified in ABCB4 in our series of cases (c.2534G>T (p.Gly845Val)) was uncertain up to this case report. The present data provide convincing evidence as to the correlation between this mutation and the clinical phenotype of PFIC 3.